PENERAPAN METODE PENGAJARAN SQ3R DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA SMP - Doviani, Belva Yulvia; Amilia, Fitri; Mijianti, Yerry; Citraningrum, Dina Merdeka (Fon : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
In the preparation of this study, the purpose of this study is to describe the application of the SQ3R teaching method (Survey, Question, Read, Recite, Review) in improving the reading ability of grade VII students at SMPN 3 Ambulu. The main problem identified is the low ability of students to understand reading texts, which is caused by the lack of interactive learning methods. The SQ3R method was chosen because of its systematic approach and proven to be effective in improving reading comprehension. The planning of this research uses a Classroom Action Research (PTK) design with two cycles, which includes the stages of planning, implementation, observation, and reflection. Data was collected through observation and testing of learning outcomes, both pre-test and post-test. The application of this method also increases student involvement in the learning process and reading motivation. Thus, the SQ3R method can be recommended as an effective strategy to improve reading comprehension skills at the junior high school level.